Rare Case of Sarcomatoid Squamous Cell Carcinoma Arising in an Ovarian Mature Teratoma - Pedrosa, Isabel Sofia de Sousa; Alpendre, Filipa da Cunha Almeida; Sousa, Rita; Dinis, Sofia Raposo; Gomes, Daniela (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Although mature cystic teratoma (MCT) is benign, malignant transformation (MT) occurs in ∼ 1% to 2% of all cases, and usually consists of squamous cell carcinoma (SCC), which accounts for ∼ 80% of the cases. Spindle-cell (sarcomatoid) carcinoma (SCSC) is an uncommon type of SCC, comprising up to 3% of all cases. The lack of characteristic symptoms and specific imaging findings may lead to preoperative misdiagnosis. Moreover, the clinicopathologic characteristics, the treatment, the prognostic factors and the mechanism of MT have not yet been well understood due to the rarity of such tumors, especially in women of reproductive age. The authors present a case of a 34-year-old patient with 14 weeks of gestation who was diagnosed with an adnexal mass suggestive of ovarian teratoma. A laparoscopy salpingo-oophorectomy was performed after 6 months of delivery, and the histological exam revealed a sarcomatoid SCC in the MCT.
Keywords: squamous cell carcinoma; ovarian mature teratoma; pregnant women